2021
DOI: 10.1111/vsu.13610
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic guidance for perineural injections of the cervical spinal nerves in horses

Abstract: Objective: To evaluate the accuracy of ultrasonographic guidance for injection near the ventral rami of the cervical spinal nerves (VRCSN).Study design: Ex vivo study. Sample population: Ten cadavers (n = 40 injections).Methods: Left and right VRCSN at C4/5 and C5/6 were infiltrated at the intervertebral foramen (IVF) under ultrasonographic guidance. A vertically orientated 3.5-MHz curvilinear probe was used to identify the craniocaudal midpoint of the articular process joint (APJ). The probe was moved ventral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Based on the pilot study findings, the ventral branch separates from the cervical nerve root and runs immediately dorsal to the vertebral blood vessels. Other studies have shown that direct visualization of the nerve is not necessary to obtain good results and other specific landmarks can be used such as immediately below the ventral margin of the cranial articular process (transducer parallel to the short axis of the neck) or the region between the APJ and the vertebral body (transducer parallel to the long axis of the neck) ( 12 , 13 ). It is however highlighted that a good understanding of the anatomy and structures within and surrounding the IVF is required to perform this procedure successfully and safely ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the pilot study findings, the ventral branch separates from the cervical nerve root and runs immediately dorsal to the vertebral blood vessels. Other studies have shown that direct visualization of the nerve is not necessary to obtain good results and other specific landmarks can be used such as immediately below the ventral margin of the cranial articular process (transducer parallel to the short axis of the neck) or the region between the APJ and the vertebral body (transducer parallel to the long axis of the neck) ( 12 , 13 ). It is however highlighted that a good understanding of the anatomy and structures within and surrounding the IVF is required to perform this procedure successfully and safely ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cadaveric studies have been performed in horses aiming at developing UG injection techniques of the cervical nerve roots and showed promising results ( 11 14 ). The study performed by Wood et al had a 73% success rate with direct contact between the injectate and the ventral ramus of the targeted cervical nerve root ( 13 ). This study focused on injecting C5 and C6 and the skin of the cadavers was removed prior to performing the injections, which altered the conditions compared to live horses ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spinal nerve traverses dorsal to the vasculature of the cervical vertebrae including the vertebral artery and vein, which run in a cranial to caudal direction. 3 Pathological changes or failure of one of these joint constructs may negatively affect the IVF. 4 Osteochondrosis and osteoarthritis are the two primary disorders that affect the cervical articular processes in horses 4,5 and cervical APJ osteoarthritis is a relatively common problem in horses, particularly in the caudal cervical region.…”
mentioning
confidence: 99%
“…12 The irritation in mild forms of APJ osteoarthritis might be treated with intra-articular or perineural steroid injection. [3][4][5][6][7][8][9][10][11][12][13][14][15] However, in severe APJ osteoarthritis accompanied by significant bony proliferation, mechanical compression may occur. In these cases, surgical intervention is the only approach to decompress the spinal canal or nerve roots.…”
mentioning
confidence: 99%